2017
DOI: 10.1016/j.ydbio.2017.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Complement component C3aR constitutes a novel regulator for chick eye morphogenesis

Abstract: Complement components have been implicated in a wide variety of functions including neurogenesis, proliferation, cell migration, differentiation, cancer, and more recently early development and regeneration. Following our initial observations indicating that C3a/C3aR signaling induces chick retina regeneration, we analyzed its role in chick eye morphogenesis. During eye development, the optic vesicle (OV) invaginates to generate a bilayer optic cup (OC) that gives rise to the retinal pigmented epithelium (RPE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 113 publications
(159 reference statements)
0
9
0
Order By: Relevance
“…This can be carried out either by enzyme complexes formed by different complement proteins (convertases) or by specific proteases, e.g., cathepsin L or cathepsin B [ 11 , 69 ]. This results in high levels of anaphylatoxins C3a and C5a, which have been associated with physiological and pathological processes in the retina [ 27 , 70 , 71 ]: Eye morphogenesis [ 31 ], sub-RPE depositions [ 32 ], pro-inflammatory RPE reaction [ 33 , 34 , 35 ], PI3/Akt-pathway activation [ 29 ], and ER stress-mediated lipid accumulation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be carried out either by enzyme complexes formed by different complement proteins (convertases) or by specific proteases, e.g., cathepsin L or cathepsin B [ 11 , 69 ]. This results in high levels of anaphylatoxins C3a and C5a, which have been associated with physiological and pathological processes in the retina [ 27 , 70 , 71 ]: Eye morphogenesis [ 31 ], sub-RPE depositions [ 32 ], pro-inflammatory RPE reaction [ 33 , 34 , 35 ], PI3/Akt-pathway activation [ 29 ], and ER stress-mediated lipid accumulation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported, that endogenous CFH and anaphylatoxins contribute to transcriptional and metabolic homeostasis of RPE cells [ 28 , 29 , 30 ]. In RPE cells complement anaphylatoxins receptor signaling is involved in eye morphogenesis [ 31 ], sub-RPE deposits [ 32 ], pro-inflammatory RPE reaction [ 33 , 34 , 35 ], PI3/Akt-pathway activation [ 29 ], and stress-mediated lipid accumulation in RPE cells [ 36 ]. Together this indicates an involvement of autocrine complement reactivity in housekeeping mechanisms maintaining RPE physiology.…”
Section: Introductionmentioning
confidence: 99%
“…In the CNS, microglia, astrocytes, oligodendrocytes, and neurons express C3aR, among which the neurons were identified as the principle cell type expressing C3aR under physiological conditions [164-167]. It has been shown that C3aR is involved in chick eye morphogenesis and rat cerebellar cortex histogenesis during development and facilitates mouse skeletal muscle regeneration after cardiotoxin-induced muscle injury [168-170]. However, in multiple CNS diseases, C3aR expression was increased in the brain, contributing to the exacerbation of inflammation and disease progression.…”
Section: Complement In Ischemic Strokementioning
confidence: 99%
“…However, increasing evidence from the last two decades has demonstrated that C3aR is also expressed by many non-immune cells and participates in various physiological and pathological processes. For examples, C3aR signaling was reported to participate in the regulation of eye morphogenesis [16], neural development [17][18], embryonic chick retina [19] and cardiac resident cell [20] regeneration, astroglial cell differentiation [21] and survival [22], diet-induced obesity and metabolic dysfunction [23], and tau hyperphosphorylation in Alzheimer's Disease [24]. Also, C3aR signaling was found to be involved in the induction of in ammatory cytokines [25], proliferation of mesangial [11] and carcinoma cells [12] and EMT of tubular epithelial cells [10].…”
Section: Discussionmentioning
confidence: 99%